Effect of whole cereal grains contained in the ration on calf performance and selected morphometric parameters of the rumen and small intestine - D. Strusińska; D. Minakowski; G. Bomba; I. Otrocka-Domagała; M. Wiśniewska; J. Tywończuk (Czech Journal of Animal Science, 2009)
The aim of this study was to determine the effect of whole maize and oat grains contained in starter concentrates on the performance of calves (during the first 90 days of their life) and selected morphometric parameters of the rumen and small intestine. The study was conducted on two groups of Holstein-Friesian calves (each of 3 males and 9 females) during the first 90 days of their life. After colostrum feeding all calves were given a milk replacer. Group 1 (control) received a concentrate (containing ground cereal grains) and meadow hay. Until 4 weeks of age group 2 (experimental) received a concentrate mixed with 25% of whole maize grains, followed by a concentrate mixed with 25% of whole maize grains and 25% of whole oat grains. The rations were supplemented with hay in the last two weeks of the experiment. Feeding the concentrates based on ground cereal components to calves (until 30 days of age) enabled to increase both feed intake and daily body weight gains. The addition of whole maize and oat grains to diets for the calves of experimental group significantly increased their mean daily gains throughout the experimental period, compared to the calves of control group (906 g vs. 769 g). At 90 days of age, the bulls of experimental group were characterised by thinner (P < 0.01) ruminal epithelium, including a thinner cornified layer (17.50 vs. 33.39 µm). Those calves also had thicker duodenal epithelium (P < 0.01) and thicker jejunal mucosa (P < 0.05). Moreover, the calves of experimental group had regular and tall intestinal villi, which were irregular in the calves of control group and varied in length and shape. The obtained results indicate that it is recommended to supplement whole maize and oat grains to diets for calves, starting from the second month of life.